Determining the Criminal Acts on the Agreement with a Series of Lies - Krisboy Joe Valentino Purba; Fenty U. Puluhulawa; Dian Ekawty Ismail (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The purpose of this writing is to analyze the enforcement ideally of the criminal act of agreement with a series of lies. This type of research is normative legal research with a legislative approach, a case approach and a conceptual approach. The analysis used in this research is descriptive analysis. The results of the study show that the ideal law enforcement against the crime of agreement with a series of lies must at least pay attention to three main aspects, namely certainty, justice and utility. Therefore, regulatory reconstruction is needed to clarify norms regarding the difference between defaults and fraud, standardize technical guidelines for special investigation of cases of agreements with lies so that the apparatus has a uniform size, strengthen the role of prosecutors in discretion, be able to resolve cases through restorative justice and strengthen legal understanding for the public through legal education or socialization.